Development of Innovation and knowledge of Agriculture Appropriate Technology by Sufficiency Economy of Philosophy Transfer to farmers in the Community, Nakhon Pathom / การพัฒนานวัตกรรมและองค์ความรู้การถ่ายทอดเทคโนโลยีการเกษตรที่เหมาะสมโดยใช้หลักปรัชญาเศรษฐกิจพอเพียงสู่เกษตรกรในชุมชนจังหวัดนครปฐม - พิทักษ์พงศ์ ป้อมปราณี, Pitakpong Pompranee / (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 1 (2558): January - April 2015, 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนานวัตกรรมและองค์ความรู้การถ่ายทอดเทคโนโลยีการเกษตรที่เหมาะสม โดยใช้หลักปรัชญาเศรษฐกิจพอเพียงสู่เกษตรกรในชุมชนจังหวัดนครปฐม โดยประยุกต์ใช้กระบวนการวิจัยชุมชนร่วมกับการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม (Participatory Action Research : PAR) โดยใช้บริบทในพื้นที่เป็นตัวตั้ง มีวิธีการศึกษา คือ 1) การศึกษาระดับความรู้ความเข้าใจของเกษตรกรในการใช้ปรัชญาเศรษฐกิจพอเพียงในกระบวนการผลิตทางการเกษตร 2) การศึกษาบริบทชุมชนในด้านระบบการผลิต และระบบนิเวศเกษตรในชุมชน และ 3) การพัฒนานวัตกรรมและกระบวนการถ่ายทอดเทคโนโลยีการเกษตรที่เหมาะสมสู่เกษตรกร โดยใช้หลักปรัชญาเศรษฐกิจพอเพียง ผลการศึกษา พบว่า เกษตรกรส่วนใหญ่มีระดับความรู้ความเข้าใจในการใช้ปรัชญาเศรษฐกิจพอเพียง ในกระบวนการผลิตทางการเกษตรในระดับปานกลาง มีความรู้ความเข้าใจแต่ขาดการปฏิบัติอย่างจริงจัง การศึกษาบริบทชุมชนในด้านระบบการผลิตและระบบนิเวศเกษตรในชุมชน พบว่า 1) ผลิตภาพหรือระดับการผลิตของชุมชนเป็นไปตามมาตรฐาน 2) เสถียรภาพหรือ ความสม่ำเสมอ เป็นไปตามมาตรฐาน 3) ถาวรภาพหรือความยั่งยืน พบว่า ทุกชุมชนอยู่ในเกณฑ์ต่ำกว่ามาตรฐาน โดยพิจารณาจากกระบวนการการจัดการดินและการจัดการศัตรูพืช 4) กิจกรรมการเกษตรในชุมชนส่งผลต่อการสร้างความสามัคคีในหมู่เพื่อนบ้านใกล้เรือนเคียงและเครือญาติ 5) กิจกรรมการเกษตรในชุมชนมีความเสมอภาคในด้านการผลิต การตลาด และผลประโยชน์ที่ต่างคนต่างได้รับตามกำลังการผลิตของตนเอง และ 6) ชุมชนมีการพึ่งตนเองด้านปัจจัยการผลิตโดยทั่วไปอยู่ในระดับต่ำกว่ามาตรฐาน การพัฒนานวัตกรรมและกระบวนการถ่ายทอดเทคโนโลยีการเกษตรที่เหมาะสมสู่เกษตรกรโดยใช้หลักปรัชญาเศรษฐกิจพอเพียง มีรูปแบบกระบวนการ 5 กระบวนการ ได้แก่ 1) การจัดกระบวนการเคลื่อนไหวทางสังคม ประกอบไปด้วย การจัดเวทีสนทนากลุ่มย่อย (เวทีสนทนายามเย็นที่บ้านเกษตรกร) การจัดเวทีสนทนากลุ่มย่อยเชิงประเด็น และการจัดเวทีวิจัยสัญจร 2) การจัดกระบวนการสร้างความรู้ ประกอบไปด้วย เวทีประชุมกลุ่มเพื่อการกำหนดความรู้ร่วมกัน กิจกรรมการอบรมให้ความรู้ในห้องบรรยาย และกิจกรรมการเรียนรู้จากแหล่งเรียนรู้ นอกพื้นที่ 3) การจัดกระบวนการกระจายความรู้ 4) การจัดกระบวนการเรียนรู้จากการปฏิบัติ และ 5) กระบวนการสร้างอัตลักษณ์เกษตรกรต้นแบบ   คำสำคัญ : การถ่ายทอดเทคโนโลยีการเกษตร  การพัฒนานวัตกรรม  เทคโนโลยีการเกษตรที่เหมาะสม               This research aims to develop an innovative and knowledge of appropriate agricultural technology transfer by the sufficiency economy philosophy to farmers in the community, Nakhon Pathom. The study was using the application of the research community with participatory action research (PAR) by using context as input. How the study was 1) to study the level of understanding of the farmers in the sufficiency economy philosophy on the agricultural production process. 2) Education in the context of production systems and agro - ecosystem in the community. 3) Development of innovative and appropriate agricultural technology transfer  process to the farmers by the sufficiency economy philosophy. The results showed that most farmers have a deeper understanding of the medium in process of agricultural production by the sufficiency economy philosophy, but lack of practice. The context of the system of production and ago - ecosystems found that 1) the productivity or production levels, according to the standards of the community. 2) Stability or consistency are the standards. 3) Permanent or sustainable community is found that all of the criteria below based on the management of soil and pest management. 4) Agricultural activities in affected communities to establish harmony among neighbors and neighborhood. 5) Agricultural activities in the community are equal in terms of production and marketing. and 6) community self-reliance, the inputs are generally lower than standard. Innovation and the transfer of agricultural technologies to farmers using the sufficiency economy philosophy. 5 process, i.e a process model. 1) The process of social mobility with a sub forum. (Forum home evening farmer) organized the forum sub-oriented issues and backstage roaming research 2) The knowledge creation process consists of the meetings to determine the knowledge-sharing activities, provide training in a lecture hall. And learning from sources outside the area. 3) Classification process of distributing knowledge. 4) The process of learning from practice and 5) Process of identity construction master-farmers.   Keywords: Agricultural Technology Transfer, Innovation Development, Agriculture Appropriate Technology
Keywords: การถ่ายทอดเทคโนโลยีการเกษตร การพัฒนานวัตกรรม เทคโนโลยีการเกษตรที่เหมาะสม Agricultural Technology Transfer, Innovation Development, Agriculture Appropriate Technology